2018
DOI: 10.1016/j.bbmt.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Conditioning Regimens BEAM and FEAM for Autologous Hematopoietic Stem Cell Transplantation in Lymphoma: An Observational Study on 1038 Patients From Fondazione Italiana Linfomi

Abstract: BEAM (carmustine [bis-chloroethylnitrosourea (BCNU)]-etoposide-cytarabine-melphalan) chemotherapy is the standard conditioning regimen for autologous stem cell transplantation (ASCT) in lymphomas. Owing to BCNU shortages, many centers switched to fotemustine-substituted BEAM (FEAM), lacking proof of equivalence. We conducted a retrospective cohort study in 18 Italian centers to compare the safety and efficacy of BEAM and FEAM regimens for ASCT in lymphomas performed from 2008 to 2015. We enrolled 1038 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Some studies have suggested that BEAC may increase the risk of cardiotoxicity 23,24 ; however, a recent large-scale retrospective matched cohort study by the European Society for Blood and Marrow Transplantation (EBMT) found comparable outcomes and toxicity profiles for ASCT conditioned with BEAM or BEAC. 15 In line with previous literature, 9,15,24 the most prevalent grade 3/4 extrahematologic toxicities in our BEAM/BEAC group were nausea/vomiting (20.7%), mucositis (14.1%), and diarrhea (13.0%). Regarding the GBM regimen, Nieto et al reported that the most common ≥grade 3 adverse events in r/r lymphoma and multiple myeloma were mucositis (27%-41%), dermatitis (7%-10%), hyperbilirubinemia (12%-19%), and elevated transaminases (9%-19%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies have suggested that BEAC may increase the risk of cardiotoxicity 23,24 ; however, a recent large-scale retrospective matched cohort study by the European Society for Blood and Marrow Transplantation (EBMT) found comparable outcomes and toxicity profiles for ASCT conditioned with BEAM or BEAC. 15 In line with previous literature, 9,15,24 the most prevalent grade 3/4 extrahematologic toxicities in our BEAM/BEAC group were nausea/vomiting (20.7%), mucositis (14.1%), and diarrhea (13.0%). Regarding the GBM regimen, Nieto et al reported that the most common ≥grade 3 adverse events in r/r lymphoma and multiple myeloma were mucositis (27%-41%), dermatitis (7%-10%), hyperbilirubinemia (12%-19%), and elevated transaminases (9%-19%).…”
Section: Discussionsupporting
confidence: 91%
“…Recent decades, however, have seen a limited availability of melphalan, leading to the emergence of alternative conditioning regimens, such as BEAC (which substitutes cyclophosphamide for melphalan), with reports indicating comparable toxicities and outcomes 13–15 . After 2010, a shortage of BCNU prompted the exploration of alternatives like bendamustine or formustine, which, while clinically effective, are associated with new adverse effects, including renal injury 9,16,17 . Additionally, MD Anderson Cancer Center developed a regimen comprising gemcitabine, busulfan, and melphalan (GBM), noted for its potent synergistic effect in inhibiting lymphoma cell line proliferation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanism of action of BCNU-induced IPS has not yet been elucidated, it appears to be dose-dependent [9]. The incidence of IPS associated with BCNU varies widely in the literature, with rates of 1-64% reported [9][10][11][12]. Unsurprisingly, BCNU doses below 450 mg/m 2 appear to be far less problematic [10].…”
Section: The Benefits Of Beeammentioning
confidence: 99%
“…With the aim of obtaining a higher anti-lymphoma activity and/or reducing the toxic effects, a number of studies suggested the possibility of improving the outcomes of NHL patients through modifing the conditioning regimens [8][9][10]. BuCyE (busulfan, cyclophosphamide, and etoposide) [11,12] and Benda-EAM (bendamustine, etoposide, cytarabine, and melphalan) [13][14] were approved to be effective and safe for NHL patients [15][16].…”
Section: Introductionmentioning
confidence: 99%